How may preferential heating of the substrate aid template-free preparation of EMT zeolite and its coatings? - Dagli, Zulfiye; Atalay-Oral, Cigdem; Tasdelen-Yucedag, Cigdem; Tatlier, Melkon (Elsevier, 2022)
The suitability of the preferential heating of the substrate by conduction for the preparation of coatings of EMT-type zeolites was investigated. For this aim, synthesis experiments were performed by using the substrate heating method and the results were compared to those obtained by conventional synthesis where the substrate is heated by convection. EMT zeolites represent an extreme case of metastability, which renders the preparation of their coatings of notable thickness quite difficult. Various synthesis conditions were tested and the coatings obtained were characterized by X-ray diffraction (XRD), field emission gun scanning electron microscopy (FEGSEM), energy dispersive X-ray spectroscopy (EDX) and thermogravimetry (TG). It was determined that template-free preparation of relatively thick EMT coatings (identified as ZSM-3, an intergrowth of EMT and FAU zeolites) was possible by using the substrate heating method. Conventional synthesis also yielded coatings of EMT-type, but with only a few microns thickness, at similar substrate temperatures. The zeolite crystallinity was improved by varying the synthesis conditions. Some coatings exhibited quite high water capacities and low regeneration temperatures, favorable for use in applications, such as adsorption heat pumps.
Keywords: EMT; Zeolite; Coating; Template-free; Synthesis